The Elementary School Teachers’ Perceptions of The Implementation of Sasak Culture-Based Learning in West Lombok - Ryya Aulia Asirri; Nuri Ashrissilmi (Indonesian Journal of Educational Innovation, 2025)
Culture-based learning is an approach designed to embrace students’ cultural diversity. This study aimed to explore elementary school teachers’ perceptions in West Lombok Regency regarding the integration of culture into science education. A quantitative survey method was employed, with data collected via questionnaires using a Likert scale. The analysis involved both descriptive and quantitative techniques, calculating the percentage of responses in each category for every indicator. Findings revealed that teachers’ understanding of Sasak culture and culture-based learning was excellent, with 82% recognition. Their attitudes toward Sasak cultural integration were also highly positive, at 85%. The implementation of Sasak culture-based learning was successful at a 75% (good), while the perceived benefits scored 85% (very good). Obstacles encountered during implementation scored 68%, indicating a good level. These results aim to provide insight into teachers’ comprehension, acceptance, and application of local culture in education, and to inform curriculum development, teacher training, and the creation of culturally relevant teaching materials.